2019
DOI: 10.1002/ptr.6392
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA combined with cisplatin synergistically inhibits non‐small‐cell lung cancer in vitro and in vivo via down‐regulating the phosphatidylinositol 3‐kinase/Akt signalling pathway

Abstract: Cisplatin represents one of the first‐line drugs used for non‐small‐cell lung cancer treatment. However, considerable side effects and the emergence of drug resistance are becoming critical limitations to its application. Combinatorial strategies may be able to extend the use of cisplatin. Both Tanshinone IIA and cisplatin inhibit non‐small‐cell lung cancer cell growth in a time‐ and dose‐dependent manner. When Tanshinone IIA was combined with cisplatin at a ratio of 20:1, they were observed to exert a synergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…9,30,31 In the past decades, Tan IIA has attracted great interest in cancer prevention and chemotherapy due to its significant antitumor efficacy and minimal side effects. Recent reports revealed that Tan IIA inhibits NSCLC cells via down-regulating the PI3K/Akt signalling 32 and activating the JNK pathway. 33 Although the induction of mitochondrial apoptosis is involved in Tan IIA-mediated antitumor activity, the molecular mechanism was not clear.…”
Section: Discussionmentioning
confidence: 99%
“…9,30,31 In the past decades, Tan IIA has attracted great interest in cancer prevention and chemotherapy due to its significant antitumor efficacy and minimal side effects. Recent reports revealed that Tan IIA inhibits NSCLC cells via down-regulating the PI3K/Akt signalling 32 and activating the JNK pathway. 33 Although the induction of mitochondrial apoptosis is involved in Tan IIA-mediated antitumor activity, the molecular mechanism was not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results indicate that the combination of cordycepin and cDDP has a synergistic effect on inhibiting apoptosis. Other studies have shown that cordycepin can inhibit the invasion and metastasis of cancer cells 29 32 . Meanwhile, through our research, we found that cordycepin and cDDP can synergistically inhibit the ability of esophageal cancer cells to invade and metastasize and associate with EMT.…”
Section: Discussionmentioning
confidence: 92%
“…Treatment with Tan IIA induced cell cycle arrest, impaired angiogenesis, invasion, and metastasis, and promoted apoptosis (34). Furthermore, Tan IIA enhanced the tumor-killing effect when combined with chemotherapy agents or radiotherapy (40,41). A panel of protein kinases has been demonstrated as potential targets in Tan IIA-treated tumor cells, such as PI3K/Akt, MAPK, and mTOR (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%